From Science to Utopia: Marcuse and Critical Utopianism - L. A. Agamalova (Социология власти)
The article examines the concept of utopia in its post-Marxist context. Since the 1970s—against the backdrop of the failures of May 68, the self-exposures of the USSR, and the decline of the workers’ movement, as well as in accordance with the immanent history of the logic of the history of philosophy itself—the concept of utopia has been running through new areas of meaning and is extremely dialectical in two modes: temporal and ontological. The first transforms utopia from never-being into “past”, the second provides two inversions, considering it as 1) a dystopia, the other of utopia, which is declared to be the hidden truth of utopia; and — when it is fundamentally possible according to its own concept — 2) as impossible, in connection with which utopia and its concept return to the discourse as a kind of empty place around which modern pessimism circles, correctly believing that the future is unimaginable. The time of ends, from the end of the grand narratives of disappointed radicals (Lyotard) to the end of politics (see Rancière’s analysis), is, however, picked up by Marcuse, who suggests considering utopia as ahistorical. The author introduces this strange ahistorical or even anti-historicalism as historical, relying on the conceptualized phenomenon of the desynchronization of the “base” (the development of productive forces to the degree necessary for social revolution) and the “superstructure”, which runs into a limit, since it cannot represent the restrained base, which has broken out of the formational “scientific” logic. When Marcuse writes that a utopia in the strict sense can now be called a project that violates the laws of nature, he means the “impossible” into which utopia turns after the catastrophes of the 20th century, betraying the truth of its concept contained in the simple possibility of another world. More than 50 years after “The End of Utopia” and almost 30 years after the ontological turn in philosophy, we can say that utopia is still unimaginable — in the strict sense is what violates the laws of logic. This thesis opens up the possibilities of a new dialectic and its alliance with transcendentalism, which the author considers as a critique of plastic reason in the spirit of Malabou, constructing time and time again the assumptions-concepts that it needs and which are “practically necessary” according to Kant.